3D‐printed wood‐polylactic acid‐thermoplastic starch composites: Performance features in relation to biodegradation treatment. Issue 36 (26th April 2021) - Lee, Danbee; Sun, Yufeng; Youe, Won‐Jae; Gwon, Jaegyoung; Cheng, Huai N.; Wu, Qinglin
Abstract: In view of the current public concern about microplastics, biodegradability of 3D‐printed polymeric materials is an important issue. In this work, we studied the effects of soil‐burial biodegradation treatment on wood‐polylactic acid (PLA) blends with three different thermoplastic starch (TPS) contents (i.e., 0, 10, and 20 wt%). The wood‐PLA‐TPS composites were 3D‐printed through the fused deposition modeling technique. The use of TPS led to reduced mechanical properties and thermal stability of the composites. Biodeterioration of the composites was clearly observed for the composite with high TPS content after the soil burial test. Thermal decomposition temperature, activation energy, and degree of crystallinity of biodegradation treated composites increased for composites with higher TPS content. The observed behavior was due to decomposed TPS and wood in the composites from biodegradation treatment, resulting in increase in the relative PLA content level. Also, the weight loss percentage of composites increased from 3.2% to 18.5% after the soil burial test as the TPS content in the composites increased from 0 to 20 wt%. The presence of TPS and wood helped improve the biodegradation of the 3D printed PLA composites, while PLA itself is not easily bio‐degraded. Abstract : Basic properties thermal degradation kinetics and crystallinity, and biodegradation weight losses as influenced by in‐door soil burial treatment were established for 3D printed wood‐PLA‐TPS composites.